THE DESIGN OF STRUCTURAL MEMBERS : with model answers to R.I.B.A. final examination questions - Jackson, Harold Thomas, author 321366 (London : The Architectural Press London, 1962)
This book is intended primarily for students of architecture who are preparing for the R.I.B.A. Final Examination; but at the same time, it will be found useful by all practising architects and assistants. It contains about a hundred and twenty typical R.I.B.A. Final Examination questions accompanied by model answers; and examples with answers are given for questions which may appear in future Final Examinations. The problems met in practice in the design of more complex structures are explained and solved. The architect, whether student, assistant or principal, requires to know the dimensions and design of the structural members of his buildings quickly and, as far as is practical, easily. This book, therefore, provides him firstly with all the necessary data, gathered from a host of different sources (Codes of Practice, British Standards, technical journals and other sources are referred to throughout). Sections deal with determinate and indeterminate structures, wind pressure, supported, fixed or continuous beams, timber floors, the various forms of steelwork, steel beams (including the new Universal beams), stanchions, connections, trussed frames, reinforced-concrete slabs, beams and columns, bases, stairways, pre-cast, pre-stressed and shell concrete, brickwork, retaining walls and pile foundations. The mathematical processes have been kept as simple as possible, and are easy to follow.